Evaluation of readability and reliability of online patient information for intracranial aneurysms. Issue 4 (29th December 2021) - Patel, Cheerag Bharatbhai; Kerr, Neal; Ahmadi, Omid; Muthu, Thirayan
Abstract: Introduction: Intracranial aneurysms are common. Receiving this diagnosis can have a profound impact on patients and their families and this is compounded by the nuanced complexities around their management. An overwhelming majority of patients research health information using the internet. Patient‐centred care and informed consent requires patients to have access to information that is readable and reliable. The aim of this study was to assess the readability and reliability of online health information about intracranial aneurysms. Method: A Google search was conducted using the terms 'brain aneurysm', 'cerebral aneurysm', and 'intracranial aneurysm' and the first 75 websites were screened for assessment. The readability of each website was assessed using the Flesch reading ease score (FRE), the Flesch–Kincaid grade level (FKGL), the gunning fog index (GFI) and the simple measure of gobbledygook (SMOG) indices. Reliability was assessed using the DISCERN instrument and the Journal of the American Medical Association benchmark criteria (JAMA). Results: Following exclusion, 36 websites were analyzed. The websites collectively scored as 'difficult' readability and 'poor' reliability on average. Statistically significant differences in readability were observed between websites categorized as patient health information and commercial compared with academic and physician. Differences in readability were also observed between search results of 'brain aneurysm' compared with 'intracranial aneurysm'. Conclusion: The readability and reliability of online health information about intracranial aneurysms is suboptimal. Health professionals must ensure their patients are well informed which includes directing them to high quality resources which are readable and reliable and use layperson‐oriented language during the consultation. Abstract : This research was completed to investigate the readability and reliability of online information about intracranial aneurysms that patients will encounter. Overall, the readability and reliability of online information on this topic was poor. Interestingly, there was a statistically significant difference in readability depending on search terms used, with the search term 'brain aneurysm' providing better readability than 'intracranial aneurysm.'